"Ke tlile bohadi" - Staying in abusive marriages: A case study of selected women in under-resourced areas of Musina in Limpopo Province - Mathebula, WN; Mafa, P; Makhubele, JC (Technium Social Sciences Journal, 2021)
Globally, cases of abused married women have become endemic. One acknowledges the fact that the majority of women are subjected to all forms of abuse, some leading to murder. In South Africa, in particular, there has been an increasing number of women abuse and murder, especially to those women who continue to stay in abusive marriages. This paper aims to develop African research lenses or perspectives in studying the phenomenon of women who continue to remain in abusive marriages. It becomes necessary to develop African lenses to reflect on this phenomenon in the light of culture and heritage as being central to African philosophy and epistemology. To that end, selected lived experiences of women will be collected for this purpose. A targeted number of women abused was interviewed and their lived experiences were collected and analysed for this purpose. The African Womanism Theory will be used in the process of guiding the study and Thematic Content Analysis will be used to make sense of the data. This paper concludes that while culture in Africa has been generally praised for its useful tenets and directions, at times it becomes oppressive.